Are client and provider preferences for HIV care coordination programme features concordant? Discrete choice experiments in Ryan White part A-funded New York City care coordination programmes - Denis Nash; Jennifer Carmona; Rebecca Zimba; Tigran Avoundjian; Chunki Fong; Madellena Conte; Honoria Guarino; Grace Herndon; Gina Gambone; Mary Kathryn Irvine (BMJ Open, 2025)
Objectives The New York City (NYC) HIV Care Coordination Programme (CCP) is designed to help people with HIV (PWH) overcome barriers to care and treatment engagement. We assessed preferences for CCP components among programme enrollees (’clients’) and providers. Our objective is to compare client and provider preferences, which were previously analysed separately.Design We used a discrete choice experiment to assess preferences for four CCP features (‘attributes’): Help with Adherence to Antiretroviral Therapy (ART), Help with Primary Care Appointments, Help with Issues other than Primary Care and Where Programme Visits Happen. Each of these attributes had 3–4 variants (‘levels’). In the original surveys, levels within Where Programme Visits Happen varied by participant type (client vs provider). We recoded the levels by visit location (VL) or by travel time (TT) to make them comparable and report results from both approaches.Setting 25 Ryan White Part A-funded NYC CCPs participated.Participants 152 providers and 181 clients completed the survey.Primary and secondary outcome measures Preferences were quantified using the relative importance of the attributes and utility of the levels.Results From January 2020 to March 2021, 152 providers and 181 clients completed the survey. Most of the providers (52%) were <40 years, while most of the clients (60.2%) were ≥50 years. Almost half of the providers identified as Hispanic, whereas two-thirds of the clients (66.9%) identified as Black non-Hispanic. Most of the providers and clients identified as women (68.4% and 55.3%, respectively). In both the VL and TT analyses, clients were most influenced by Help with Adherence to ART (relative importance (RI) 30.5%, 95% CI 28.5% to 32.4% and 29.4%, 95% CI 27.5% to 31.4%, respectively), preferring medication reminders via phone or text, and Where Programme Visits Happen (RI 26.8%, 95% CI 25% to 28.6% and 32%, 95% CI 30.1% to 33.8%, respectively), preferring visits via phone or video chat. In the VL analysis, providers were most influenced by Help with Issues other than Primary Care (RI 26.9%, 95% CI 25.3% to 28.6%), valuing connections to specialty medical care, and by Help with Adherence to ART (RI 25.5%, 95% CI 23.5% to 27.5%), valuing directly observed therapy most highly. In the TT analysis, providers were most influenced by Where Programme Visits Happen (RI 28.2%, 95% CI 26.6% to 29.9%), preferring longer travel times, and Help with Issues other than Primary Care (RI 24.5%, 9%% CI 22.9% to 26.1%), again preferring connections to specialty medical care.Conclusions Client and provider preferences clearly diverged regarding CCP service intensity: in the aggregate, clients tended to prefer lower-intensity services, whereas providers endorsed higher-intensity services. These results highlight the importance of engaging clients as partners in decisions about programme services to facilitate alignment with client values.